ORGANIZATIONAL COMPROMISE OF PUBLIC UNIVERSITY EMPLEYEE´S - Loli Pineda, Alejandro (2007)
This article a study carried out in a sample of 72 subjects in order to investigate the commitment of workers for organization where they work and the relationship between organizational commitment and demographic variables. The results show that the majority have a normal level of commitment to organization and that no relationships exist with the demographic variables used in this analysis. A cross-analysis between the factors of organizational commitment shows that a significant relationship exists between some of them.